2018
DOI: 10.1039/c8ee00816g
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for high transition metal capacity in disordered rocksalt Li-ion cathodes

Abstract: The discovery of facile Li transport in disordered, Li-excess rocksalt materials has opened a vast new chemical space for the development of high energy density, low cost Li-ion cathodes. We develop a strategy for obtaining optimized compositions within this class of materials, exhibiting high capacity and energy density as well as good reversibility, by using a combination of low-valence transition metal redox and a high-valence redox active charge compensator, as well as fluorine substitution for oxygen.Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
200
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(214 citation statements)
references
References 66 publications
14
200
0
Order By: Relevance
“…[10,19] Within the LiF-LiMnO 2 -LiNbO 3 system, the cluster expansion consisting of pair interactions up to 7.1 Å, triplet interactions up to 4.0 Å, and quadruplet interactions up to 4.0 Å based on a primitive rock salt lattice was constructed using DFT-calculated energies. [10,19] Within the LiF-LiMnO 2 -LiNbO 3 system, the cluster expansion consisting of pair interactions up to 7.1 Å, triplet interactions up to 4.0 Å, and quadruplet interactions up to 4.0 Å based on a primitive rock salt lattice was constructed using DFT-calculated energies.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[10,19] Within the LiF-LiMnO 2 -LiNbO 3 system, the cluster expansion consisting of pair interactions up to 7.1 Å, triplet interactions up to 4.0 Å, and quadruplet interactions up to 4.0 Å based on a primitive rock salt lattice was constructed using DFT-calculated energies. [10,19] Within the LiF-LiMnO 2 -LiNbO 3 system, the cluster expansion consisting of pair interactions up to 7.1 Å, triplet interactions up to 4.0 Å, and quadruplet interactions up to 4.0 Å based on a primitive rock salt lattice was constructed using DFT-calculated energies.…”
Section: Methodsmentioning
confidence: 99%
“…d. Recent work [10] has demonstrated that the strong LiF bond limits the amount of Li that can be removed from the coordination shell of a F − anion. d. Recent work [10] has demonstrated that the strong LiF bond limits the amount of Li that can be removed from the coordination shell of a F − anion.…”
Section: Materials Design and Electrochemical Performancementioning
confidence: 99%
See 3 more Smart Citations